Investigating the Perceptions of Community Health Nurses Towards Home Visits in Blantyre Urban Health Centres - Chikuni, Dorothy Mpawa (Kamuzu University of Health Sciences, 2022)
The primary purpose of this study is to investigate community health nurses' perceptions on home visits in urban Blantyre health centres in Blantyre district. A descriptive qualitative research design with purposeful sampling will be used in this study. The sample will consists of ten enrolled CHN working in the area of study. The data collection methods will be an in depth face to face interview with the respondents. The data will be analyzed manually using content analysis. Conclusion will be made according to findings of enrolled CHNs' perceptions towards home visits. The recommendations will include the strengths, weaknesses and suggestions of the researcher.